Measuring arguments from order for Q - Tripp, Jeffrey M. (Neotestamentica, 2013)
The argument from order for the two-document hypothesis is central to the claim that Q is a unified document rather than a collection of shorter documents or shared oral tradition. Once double tradition material is extracted from Matthew and Luke and paired, the argument becomes essentially mathematical. Previous attempts at measuring the degree of agreement have rarely included detailed methodological discussions. Hence these measurements derive from loosely defined or implied methodologies influenced by subjective choices of the scholar, making it impossible to judge the relative probabilities of their results. This article proposes a new statistical metric borrowed from regression analysis, the coefficient of determination (R2). This metric is then applied to influential tables of double tradition material to determine the strength of their agreement. As will be demonstrated, these tables do not provide strong evidence of a unified document behind double tradition material based on order alone.